The Effect of Leadership Effectiveness and Interpersonal Communication on Teacher Job Satisfaction - Jahro, Listi; Harapan, Edi; Tahrun, Tahrun (Journal of Social Work and Science Education, 2021)
The purpose of this ex post facto correlational study is to investigate the impact of leadership effectiveness and interpersonal communication on teacher job satisfaction at SMA Sub Rayon III Prabumulih City. A questionnaire was utilized as the study tool. Inferential statistics, such as the basic linear correlation test, multiple linear regression, t-test, and F-test, were used to assess the data. The findings revealed a substantial relationship between leadership effectiveness and interpersonal communication and teacher job satisfaction at SMA Sub Rayon III Prabumulih. This research assists the principal in establishing effective communication in the school environment in order to achieve teacher job satisfaction.